Nursing students’ learning strategies for e-learning during the Covid-19 pandemic in Iran: a qualitative study - Nesa Cheraghbeigi; Shahram Molavynejad; Dariush Rokhafroz; Nasrin Elahi; Eisa Rezaei (BMC Medical Education, 2023)
Abstract Background In response to the emergency brought about by the Covid-19 pandemic, many universities around the world had to change their teaching methods from in-person classes to e-learning. The purpose of this study was to identify the learning strategies of nursing students in e-learning during the pandemic. Methods This study had a qualitative design and used content analysis approach to collect and analyze the data. Sixteen semi-structured interviews were conducted with 12 Iranian undergraduate nursing students who were selected using purposive sampling method. Results Most nursing students in this study generally used two different strategies for e-learning, namely self-centered learning strategies and collaborative learning strategies. Some students, on the other hand, adopted a passive approach in which they did not take any effective action to contribute to their learning. Conclusion In e-learning during the pandemic, students adopted different learning strategies. Therefore, designing teaching strategies tailored to the students’ strategies can promote their learning and academic achievement. Also, knowledge of these strategies helps policy makers and nursing educators to take necessary measures in order to optimize and facilitate student learning in an e-learning environment.